2005
DOI: 10.1002/ejic.200500466
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Homogeneous Catalysis

Abstract: This review article illustrates possible aspects for molecularweight enlargement and immobilisation of transition-metal complexes that have been developed for bridging the gap between homogeneous and heterogeneous catalysis. The recycling of homogeneous catalysts can be performed using different types of supports, such as dendrimers, hyperbranched polymers, nanostructured materials or stabilized nanoparticles in combination with suitable filtration methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 56 publications
0
43
0
1
Order By: Relevance
“…[19,20] These techniques include microwave assistance, the use of immobilized reagents and catalysts as well as new fluids such as supercritical CO 2 and ionic liquids. [21] Membrane reactors or nanofiltration devices are commonly required when the reagent or catalyst operates as a size enlarged species in solution [22] by being attached to soluble solid phases, dendrimers or other tags. [23] However, a critical view on flow system reveals that various aspects must be encountered.…”
Section: Definitionsmentioning
confidence: 99%
“…[19,20] These techniques include microwave assistance, the use of immobilized reagents and catalysts as well as new fluids such as supercritical CO 2 and ionic liquids. [21] Membrane reactors or nanofiltration devices are commonly required when the reagent or catalyst operates as a size enlarged species in solution [22] by being attached to soluble solid phases, dendrimers or other tags. [23] However, a critical view on flow system reveals that various aspects must be encountered.…”
Section: Definitionsmentioning
confidence: 99%
“…A wide variety of soluble supports, e.g., linear or dendrimeric polymers, [26] has been introduced to transition metal complexes through different strategies, e.g., covalent or non-covalent bonding, cluster, or colloid formation [27][28][29] ; in some cases their perfomance was even demonstrated and analyzed in continuously operated membrane reactors. [30][31][32][33][34][35][36][37][38][39] Among the different classes of supports, star-shaped polymers are remarkable candidates. A dendritic structure, which is peripherily substituted, can lead to the formation of a high loading catalyst with good solubility (chemzyme) due to the globular shape of the respective polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Although there are numerous examples of catalyst recovery, especially via precipitation, the field of nanofiltration in homogeneous catalysis is still rather unexploited, because advanced membrane reactor technology is usually needed. [7,[17][18][19][20] Recently, Rothenberg et al demonstrated, however, that this is not necessarily required and that a Ru-based transfer hydrogenation catalyst can efficiently be recovered with a relatively simple set-up. [21] We report here on the synthesis of multiple phosphine ligands attached to a dendritic support via click chemistry.…”
mentioning
confidence: 97%
“…These methods can be roughly divided in biphasic catalysis [3][4][5] and immobilization on insoluble (heterogenization) and soluble supports (molecular weight enlargement, MWE). [6][7][8] MWE catalysts can, in principle, be recovered by means of precipitation, ultracentrifugation or nanofiltration. [9][10][11][12][13][14][15][16] Although there are numerous examples of catalyst recovery, especially via precipitation, the field of nanofiltration in homogeneous catalysis is still rather unexploited, because advanced membrane reactor technology is usually needed.…”
mentioning
confidence: 99%